META ANALISIS PENERAPAN PEMBELAJARAN BERDEFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Jumrianti; St. Syamsudduha; Suhardiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of the Independent Learning policy is motivated by a learning process that is not fully oriented to the needs, characteristics, and interests of students, resulting in boredom and low learning engagement. This condition requires the implementation of student-centered learning methods, one of which is through differentiated learning. Therefore, this meta-analysis study aims to analyze the effect of the application of differentiated learning in improving student learning outcomes. The method of this meta-analysis research is formulating the problem, collecting data, coding data, analyzing data, and concluding. The results of the article search obtained 20 articles on differentiated learning to improve learning outcomes, and only 18 articles met the criteria for meta-analysis research on the application of differentiated learning. The results show that differentiated learning has a very high effect on learning outcomes, indicated by the majority of effect size values in the very large category with a p-value <0.05, indicating a significant effect. The summary effect of 1.694 with a confidence interval of 88.3% (1.245–2.144) indicates that differentiated learning consistently improves student learning outcomes. Publication bias tests using a Funnel Plot and Fail-Safe N showed that the research results were not affected by publication bias, with a Fail-Safe N value of 4.285, exceeding the recommended tolerance limit. Thus, differentiated learning has proven effective and feasible to be implemented to improve student learning outcomes